SISTEM BAGI HASIL PADA USAHA PENANGKAPAN IKAN DI KELURAHAN LAPPA, KECAMATAN SINJAI UTARA, KABUPATEN SINJAI - Nurliani Nurliani; Andi Asni; Ida Rosada; Saida Saida; Nur Fadilla (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2023)
The aim of the research is to describe the cooperation agreement between ship owners and fishermen based on the type of ship, calculate operational costs, catch value, income and analyze the profit-sharing system between ship owners and fishermen. The sample was determined using proportional random sampling by taking 10% of the population of 209 ship owners. Using descriptive analysis methods, profit analysis, and profit-sharing system analysis. The results of the research show: 1) cooperation agreements between ship owners and fishing workers are carried out verbally and have been passed down from generation to generation, 2) fishing operations on motor boats go through pre-exploitation, exploitation (fishing ground) and post-exploitation (marketing) stages, while in Outboard motorboats prepare fishing permit documents, check the condition of the ship and fishing equipment, prepare provisions, crew, and determine the fishing area, 3) average operational costs and catch value for motorboats are IDR 7,289,500 and IDR 25,358,333, respectively. outboard motor boat type Rp. 459,500 and Rp. 4,150,000, 4) profit sharing system between motor boat owner and worker fishermen on motor boat type, namely 50%:50% (boat owner Rp.9.036.000 fisherman Rp. 1,666,387/ person), while between outboard motor boat owners and working fishermen it is 60%:40% (boat owner IDR 2.214.300: fisherman IDR 1,476,200/person